APLIKASI METODE TRANSFORMASI RADON UNTUK ATENUASI MULTIPEL PADA PENGOLAHAN DATA SEISMIK 2D LAUT DI PERARIRAN “X” - Nona Dili Maricci; Agus Setyawan (Youngster Physics Journal, 2015)
Multipel in marine seismic data is the noise formed due to the high impedance contrast at he boundary between layer. Multipel interfers the data processing that will also affect the interpretation of subsurface image. Radon transformation is one of the methods to attenuate the multipel. Radon transformation method is to transform the data of the domain time-offset (t-x) into a domain intercept time- ray parameter (τ-p). Primary wave and multipel will be separated with muting desain in domain (τ-p). At the end of this study to compare the result stacking preprocessing and stacking Radon. The result of the research shows that multipel in time 190-200 ms are attenuated.